Change Of Public Accounting Firm: Analysis Based On Ceo Turnover And Modified Audit Opinions - Denny Putri Hapsari; Herman Wijaya; Nana Umdiana (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
This study aims to determine the factors that can affect the turnover of Public Accounting Firms. The factors used are CEO (Chief Executive Officer) changes and audit opinions. The population of this study is mining companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. To obtain samples with the required criteria use the purposive sampling method. Hypothesis testing is done by logistic regression due to the dependent variable, which is the change of public accounting firm used is a dummy. The results of this test indicate that (1) the CEO (Chief Executive Officer) change has a significant effect on the change in the Public Accounting Firm (2) Audit opinion has no significant effect on the change in the Public Accounting Firm.